2012
DOI: 10.1155/2012/624168
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil-Related Enterocolitis and Weight Loss: A Pediatric Case Series

Abstract: Mycophenolate mofetil (MMF) is an immunosuppressive medication utilized in the management of both autoimmune and solid organ transplant patients. Diarrhea is a common gastrointestinal side effect of MMF, but more severe forms of GI symptoms are described in renal transplant patients with a distinct pattern of histopathologic change, similar to graft-versus-host disease or Crohn's disease. This rare entity, commonly referred to as “MMF-related enterocolitis,” has been described in adult patients, mostly in rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In 2 wild-type strains (C57BL/6 and BALB/c), and in Rag1-deficient mice, we have shown that MMF treatment leads to rapid and significant weight loss accompanied by gross colonic changes and inflammation, recapitulating the effects seen in humans. 36,37 We also observed that MMF administration prompted alterations in the composition of the microbiota and its associated metagenome. The presence of the microbiota appears to be a critical factor necessary for the toxicity of MMF, as weight loss and colonic pathology were absent in GF mice, and the administration of antibiotics was sufficient to both prevent and reverse the phenotype associated with MMF exposure.…”
Section: Discussionmentioning
confidence: 71%
“…In 2 wild-type strains (C57BL/6 and BALB/c), and in Rag1-deficient mice, we have shown that MMF treatment leads to rapid and significant weight loss accompanied by gross colonic changes and inflammation, recapitulating the effects seen in humans. 36,37 We also observed that MMF administration prompted alterations in the composition of the microbiota and its associated metagenome. The presence of the microbiota appears to be a critical factor necessary for the toxicity of MMF, as weight loss and colonic pathology were absent in GF mice, and the administration of antibiotics was sufficient to both prevent and reverse the phenotype associated with MMF exposure.…”
Section: Discussionmentioning
confidence: 71%